Plan de manejo integral de residuos sólidos en la Comunidad Puerto Ébano del Cantón Sucre. - Cedeño Vargas, Gema Monserrate (2018)
The objective of the research was to establish a management plan for waste and solid waste generated in the urban sector of the Puerto Ébano Community belonging to the Canton of Sucre, requesting the Municipal GAD the socioeconomic information and documents based on the management of the Community waste. in general, as well as the georeferencing of the study site to obtain a location map, then the sample size was determined to apply the surveys to the inhabitants, calculating the number of people, monitoring was implemented to determine, the generation per capita , humidity and physical composition was characterized, creating management plans to improve the environmental quality of the locality.